2019
DOI: 10.3390/su11226480
|View full text |Cite
|
Sign up to set email alerts
|

Role of SME in Poverty Alleviation in SAARC Region via Panel Data Analysis

Abstract: The key objective of the formation of the South Asian Association of Regional Cooperation (SAARC) is to join hands collectively for slow economic growth, poverty eradication, deprived health and education sectors. In the 12th SAARC Summit, it has been declared that poverty eradication is the main area of concentration and SAARC countries would strive their best to minimize all types of poverty with the help of any possible strategy. The main objectives of the current study are to evaluate the development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
5
32
2
4
Order By: Relevance
“…His study recommended the importance of simplify procedures to access finances and reduce the cost of credit. This empirical finding is supported by a study carried out by Manzoor et al (2019) through analysis with a data panel model in SAARC. Furthermore, Kowo, Adenuga, and Sabitu (2019), using analysis of variance, coefficient of correlation, and regression analysis, found that the development of SMEs influences poverty in Nigeria.…”
Section: Literature Surveysupporting
confidence: 64%
See 4 more Smart Citations
“…His study recommended the importance of simplify procedures to access finances and reduce the cost of credit. This empirical finding is supported by a study carried out by Manzoor et al (2019) through analysis with a data panel model in SAARC. Furthermore, Kowo, Adenuga, and Sabitu (2019), using analysis of variance, coefficient of correlation, and regression analysis, found that the development of SMEs influences poverty in Nigeria.…”
Section: Literature Surveysupporting
confidence: 64%
“…Earlier studies found a significant influence of MSMEs on the number of job vacancies (Herman 2012;Hussain, Bhuiyan, and Said 2017;Rotar, Pamić, and Bojnec 2019) and economic growth (Beck, Demirguc-Kunt, and Levine 2005;Manzoor et al 2019). As Manzoor et al (2019) observe, SMEs are economy growing machines, and there is a positive correlation between the growth of SMEs and a rising economy. The mechanism of economic growth can further reduce poverty.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations